2017
DOI: 10.1515/jcim-2016-0141
|View full text |Cite
|
Sign up to set email alerts
|

The effect of celery (Apium graveolens L.) on fertility: A systematic review

Abstract: Background Fertility and infertility problems are among the complex issues in medicine. The use of herbal products in the treatment of fertility has been considered as an alternative to synthetic drugs. Celery containing known compounds can have an impact on the fertility rate. The aim of this study was to do a systematic review on conducted studies in conjunction with the celery and reproduction. Methods Required papers were searched from databases like Science direct, PubMed, Scopus, and Springer. Keywords u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
7
0
3
Order By: Relevance
“…Similarly, the aqueous extract of the leaves was observed to improve the spermatogenesis process and could be useful for some sperm fertility parameters [126]. In another study, hydroalcoholic extract of the plant was shown to boost spermatogenesis and, as indicated by this study, celery can have a protective effect against substances that cause damage to the testicular structure and spermatogenesis [199].…”
Section: Reproductive Issuesmentioning
confidence: 66%
“…Similarly, the aqueous extract of the leaves was observed to improve the spermatogenesis process and could be useful for some sperm fertility parameters [126]. In another study, hydroalcoholic extract of the plant was shown to boost spermatogenesis and, as indicated by this study, celery can have a protective effect against substances that cause damage to the testicular structure and spermatogenesis [199].…”
Section: Reproductive Issuesmentioning
confidence: 66%
“…As well as two reviews published by Kooti et al (2016, 2018), in this review we searched the information on this genus from databases (using Elsevier, ACS, Springer, Wiley, Nature, RSC, Medline Plus, Bentham Science, Hindawi Science, CNKI, VIP, Web of Science, Google Scholar and Baidu Scholar) and libraries, and the search languages were set to English and Chinese. We didn’t set the time period for searching more literatures.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is effective for treating induced HC; however, it cannot wholly eradicate the challenging symptoms of HC in 25% of CP-treated cases [9]. erefore, it is essential to involve other protective antioxidant agents such as celery seed oil (CSO) or manuka honey (MH) beside mesna to reduce the hazards of induced HC [10,11]. Numerous studies focused on celery (Apium graveolens) and honey as effective antioxidants, which substantially reduced the cellular oxidative damage [12,13].…”
Section: Introductionmentioning
confidence: 99%